ARBOLITCONCRETE ON SILICATESODIUM COMPOSITE BINDER AND SCRAPS OF VINE - Z. A. Manturov; A. O. Omarov; A. B. Toturbiev; U. D. Toturbieva (Вестник Дагестанского государственного технического университета: Технические науки)
Aim.The results of experimental studies produce siliсatеsodium composite binder of calcareous stone sawing waste, anhydrous sodium silicate, and based on them wood concrete using as an organic filler vine cuttings for the production of heat-insulating, heat-insulating, structural and structural wall material.Methods.The main technological operations of the developed arbalitconcrete are given : preparation of a composite binder; production of organic filler from the vine; preparation of arbolit concrete mass; formation of arbolit concrete mass; low-temperature treatment (drying).Results. It is found that the composite binder derived from waste stone sawing and anhydrous sodium silicate at their joint fine grinding (Ssp = 3000 cm2 / g), acquires binding properties and with the appropriate seal and heat treatment hardens and gains strength characteristics sufficient for making arbolitconcrete using crushed vine.Conclusion. It was determined that arbolitobeton obtained on the basis of the crushed vine and silikatnatrievogo composite binder strength exceeds arbolitobetona from other types of binders and organic fillers of vegetable origin.